Evaluation of Groundwater Recharge Estimates in a Partially Metamorphosed Sedimentary Basin in a Tropical Environment: Application of Natural Tracers - Felix Oteng Mensah; Clement Alo; Sandow Mark Yidana (The Scientific World Journal)
This study tests the representativeness of groundwater recharge estimates through the chloride mass balance (CMB) method in a tropical environment. The representativeness of recharge estimates using this methodology is tested using evaporation estimates from isotope data, the general spatial distribution of the potential field, and the topographical variations in the area. This study suggests that annual groundwater recharge rates in the area ranges between 0.9% and 21% of annual precipitation. These estimates are consistent with evaporation rates computed from stable isotope data of groundwater and surface water in the Voltaian Basin. Moreover, estimates of groundwater recharge through numerical model calibration in other parts of the terrain appear to be consistent with the current data in this study. A spatial distribution of groundwater recharge in the area based on the estimated data takes a pattern akin to the spatial pattern of distribution of the hydraulic head, the local topography, and geology of the terrain. This suggests that the estimates at least qualitatively predicts the local recharge and discharge locations in the terrain.